2016
DOI: 10.1016/j.jnutbio.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxytyrosol on cardiovascular biomarkers in experimental diabetes mellitus

Abstract: The aim of this study was to assess the influence of hydroxytyrosol (HT) on cardiovascular biomarkers and morphometric parameters of the arterial wall in streptozotocin-diabetic rats. Seven groups of rats (N=10 per group) were studied for 2 months: nondiabetic rats (NDR), diabetic rats treated with saline (DR) and DR treated with HT (0.5, 1, 2.5, 5 and 10 mg kg day p.o.). DR had higher platelet aggregation values, higher thromboxane B, plasma lipid peroxidation, 3-nitrotyrosine, oxidized LDL (oxLDL), myelopero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…In a clinical trial enrolling healthy volunteers, it has been demonstrated that sunflower oil supplemented with HT decreased vascular cell adhesion protein (VCAM-1) plasmatic concentration (45–50 mg/kg/day × 3 weeks) [89] and monocyte chemoattractant protein-1 and interleukin-8 receptor expression (366 mg/kg/day × 3 weeks) [87]. Such results were confirmed in rodent models, where HT reduced platelet aggregation, VCAM-1 and IL-1β expressions (0.5 to 10 mg/kg/day × 2 months) [84] and TNF-α expression (0.04%) [74]. Interestingly, Gonzalez et al [60] reported that HT (4 mg/kg/day × 2 months) reduced the size of atherosclerotic lesions in rabbits fed with a high fat and high cholesterol diet.…”
Section: Associated Complications: Oxidative Stress Inflammationmentioning
confidence: 94%
See 2 more Smart Citations
“…In a clinical trial enrolling healthy volunteers, it has been demonstrated that sunflower oil supplemented with HT decreased vascular cell adhesion protein (VCAM-1) plasmatic concentration (45–50 mg/kg/day × 3 weeks) [89] and monocyte chemoattractant protein-1 and interleukin-8 receptor expression (366 mg/kg/day × 3 weeks) [87]. Such results were confirmed in rodent models, where HT reduced platelet aggregation, VCAM-1 and IL-1β expressions (0.5 to 10 mg/kg/day × 2 months) [84] and TNF-α expression (0.04%) [74]. Interestingly, Gonzalez et al [60] reported that HT (4 mg/kg/day × 2 months) reduced the size of atherosclerotic lesions in rabbits fed with a high fat and high cholesterol diet.…”
Section: Associated Complications: Oxidative Stress Inflammationmentioning
confidence: 94%
“…Given the fact that OLE is degraded into HT, the question arose if the blood pressure lowering effect was due to OLE or HT. Lopez-Villodres et al [84] found that HT supplementation (10 mg/kg/day × 2 months) increased in diabetic rats the levels of nitrites and nitrates, potent donors of NO acting as vasorelaxing agent. In addition, Storniolo et al [85] demonstrated that HT (10 µM) counteracted hyperglycemia-induced endothelin-1 expression, a well-known hypertensive agent, in a more extend than oleic acid.…”
Section: Hydroxytyrosol and Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HXT consumption can regulate glutathione concentration and provides antioxidant enzymes to adipose tissue [ 32 ]. Moreover, in other in vivo study with experimentally induced diabetes mellitus in rats, it was shown that the HXT consumption influenced the major biochemical processes leading to diabetic vasculopathy and reduced cell proliferation in the vascular wall [ 33 ]. It is confirmed the prevention against damage by oxidative stress induced by this compound, which acted as regulator of cell protection and damage induction, controls the intracellular redox state.…”
Section: The Role Of Hxt In Healthmentioning
confidence: 99%
“…2 In the last years, scientific evidence has accumulated pointing to the pleiotropic effects of HT on multiple targets. In fact, demonstrated beneficial effects of HT for human health include its antidiabetic, 3,4 antifungal, 5 antiinflammatory, 6 antiparasitic, 7 cardio- 8 and neuroprotective 9 activities. HT has also beneficial effects on metabolic syndrome 10 and antitumoral effects of HT have been reported.…”
Section: Introductionmentioning
confidence: 99%